Effectiveness of integrating multiple intelligence theory in English teaching and learning: a systematic literature review / Syamira Nadia Hairudin ... [et al.] - Hairudin, Syamira Nadia; Ariffin, Kamisah; Ibrahim, Mohamad Nor Afandi; De Mello, Geraldine; Husin, Misyana Susanti; Nur Hidayatulshima Omar, Nur Hidayatulshima Omar; Ishak, Nurhamizah (Universiti Teknologi MARA, 2023)
A systematic literature review (SLR) can help to guide the evolution and the research fields, recommend a categorization, and helps to determine the primary issues to demonstrate current and future research directions and theoretical development that will help with the research. This SLR aims to highlight and summarise the effectiveness of integrating the multiple intelligence theory in English teaching and learning. It employed a four-step method for the systematic evidence syntheses review method which were 1) question formulation, 2) systematic searching, 3) quality assessment, and 4) data extraction, from two primary databases; Web of Science and SCOPUS, and a supporting database which is Google Scholar. The analysis pointed out to these main themes: teaching effectiveness and student attributes. The former consisted of three subthemes which were teaching strategies, teaching materials and student interests, while the latter suggested two subthemes of gender and social development. This SLR offers beneficial insights into the current research limitations and to provide recommendations on future study areas or directions. It helps to facilitate critical discussions and to be able to make such comparisons to previous research outcomes.